Pengenalan Teknologi Mikrokontroler dan Internet of Things (IoT) dalam Mendukung Keterampilan Abad 21 - Zainuddin Zainuddin; Mushaf Mushaf; Bakhrani A. Rauf; Syamsidah Syamsidah; Yasdin Yasdin (DEDIKASI, 2026)
Abstract. The rapid advancement of digital technology in the era of the Industrial Revolution 4.0 and Society 5.0 requires university students to possess 21st-century skills, including critical thinking, creativity, collaboration, and communication. However, observations conducted among students in higher education institutions indicated that many students still lack adequate understanding and practical experience related to microcontroller and Internet of Things (IoT) technologies. This community service program aimed to enhance students’ technological literacy through hands-on microcontroller and IoT training using Arduino and ESP32 platforms with a Project-Based Learning (PjBL) approach. The implementation stages included socialization, training, technology application, mentoring, and evaluation. The results demonstrated significant improvement in students’ understanding of microcontroller and IoT concepts, enhanced practical skills, and the successful development of simple IoT-based projects such as smart lamps and temperature monitoring systems. Furthermore, the program supported the development of 21st-century competencies through collaborative activities and project presentations. This initiative positively contributed to improving technology-based learning quality in higher education and is expected to be sustainable through the provision of modules, instructional media, and continuous mentoring. Keywords: Microcontroller, Internet of Things, ESP32, Project-Based Learning, 21st-Century Skills.